ANALISIS FORENSIK BUKTI DIGITAL PADA KEJAHATAN PEMBUNUHAN BERENCANA MENGGUNAKAN METODE NATIONAL INSTITUTE OF JUSTICE - Triyanto, Ageng Restu; Fachri, Fahmi (JIPI (Jurnal Ilmiah Penelitian dan Pembelajaran Informatika), 2024)
Flashdisks and SSDs are storage devices that are widely used, because even flashdisks have various capacities but still have a minimalist shape making it easy to carry anywhere. Apart from the large number of flashdisk users, SSDs are also widely used because most laptops now use SSDs as storage media, because SSDs can be said to be much better storage compared to laptops which still use HDDs for storage media, because SSDs use NAND Flash chips which are used for storage. save data. As storage media continues to develop, it is possible that it will be used in negative ways or for criminal acts, such as storing crime data and then deleting it permanently in an effort to eliminate traces of crimes that have been committed. This research uses a scenario where evidence data is then permanently deleted, with the aim of restoring data that has been deleted, including deleting data on Flashdisks and SSDs. In an effort to recover data, researchers use the FTK Imager and Autopsy tools. The data found will be analyzed using the National Institute of Justice (NIJ) method to find the percentage results of whether the data items obtained are valid with the authenticity of the evidence sought. The conclusion of this research is the use of the National Institute of Justice (NIJ) method, namely sequencing the stages of digital forensics starting from identification, collection, examination, analysis and reporting in the analysis to determine the percentage of authenticity of evidence.